Association of Socioeconomic Status and Lifestyle Factors of Polycystic Ovarian Disease among Women in a Tertiary Care Hospital in Dhaka (Sir Salimullah Medical College Journal, 2025)
Background: Polycystic Ovarian Disease (PCOD) is a prevalent endocrine disorder affecting 5–18% of women of reproductive age worldwide, with South Asia showing particularly high rates. PCOD is associated with menstrual irregularities, infertility, hyperandrogenic symptoms, and long-term metabolic risks such as obesity, diabetes, and cardiovascular disease. Lifestyle factors, including sedentary behavior, poor diet, inadequate sleep, and stress, play a central role in disease onset and progression, and urbanization has contributed to the rising prevalence in the region. The study aim was to assess the association of socioeconomic status and lifestyle factors with the risk of Polycystic Ovarian Disease (PCOD) among women in a tertiary care hospital in Dhaka. Methods: This cross-sectional study included 50 women with clinically diagnosed PCOD attending the Outpatient Department of Obs and Gynae, Bangladesh Medical University, Dhaka, Bangladesh. The duration was 12 months, from July 2024 to June 2025. Data were collected through structured interviews, clinical assessments, and anthropometric measurements. Statistical analysis using SPSS 26 included descriptive statistics, chi-square tests, Pearson correlations, and logistic regression to identify significant predictors of PCOD. Results:Among 50 women with PCOD (mean age 24 years), all were overweight/obese, 92% reported a sedentary lifestyle, and 36% consumed fast food ≥3 times weekly; 42% slept